Caracterización de Procesos y Propuesta de Mejora Continua bajo la Filosofía kaizen para Segmac Servicios Integrales (2022)
The present degree work, has as purpose establish the characterization of processes and propose a methodological design of continuous improvement with the use of lean manufacturing tools, the development of the project is contemplated under investigation mixed type, because quantitative and qualitative variables are studied, with approach of type exploratory and explanatory, because through the investigation instruments primary collection will be used for the analysis and obtaining of information; for the development of this work it was implemented a phased methodology, the first phase is of diagnostic where was identified the composition of the company object of study, in order to describe and identify the predominant features of your organizational culture, processes and threads were identified, and the waste that were presented, in the second phase a review of secondary information was carried out, in this they were identified and select, the tools that can be implemented, in the third phase of design to elaborate the formats and records, as a proposal for continuous improvement